Citizen science in marine litter research: A review. (September 2022) - Kawabe, L.A.; Ghilardi-Lopes, N.P.; Turra, A.; Wyles, K.J.
Abstract: Citizen science (CS) can help to tackle the emerging and worldwide problem of marine litter (ML), from collecting data to engaging different stakeholders. We reviewed what and how the scientific literature is reporting CS on ML to identify possible gaps to be improved. The 92 search results (separate occasions when 48 different CS initiatives were discussed across 85 publication records) revealed an under-representation of studies in developing regions. Most search results focused on the science of ML, whilst information regarding citizen scientists was commonly vague or missing, preventing critical analysis of good practices on this aspect. The studies concentrated on the shoreline and did not harmonize types and sizes of items collected, thus precluding data meta-analyses. The standardisation of CS methods and approaches and the detailed report of aspects related to citizen scientists are essential to support the science we need for the advances in CS efforts to face ML. Graphical abstract: Graphical abstract. The systematic review of the marine litter citizen science literature revealed that the aspects related to the citizen scientists are rarely reported with evidence and the report of marine litter is detailed, but biased in terms of litter size (generally macrolitter), sampled environment (mainly sandy beaches) and spatial distribution (few studies carried out on Africa). Unlabelled Image Highlights: We performed a systematic review of the marine litter citizen science literature. Reporting of marine litter is detailed, but biased to macrolitter and sandy beaches. Citizen scientists' aspects (e.g., engagement, training) is rarely reported fully with evidence. Global spatial distribution of studies is biased towards Europe and North America. Standardisation of methods and the reporting of citizen scientists' aspects are recommended.